GE_GERICHTE C/4250/2013 vom 28. Januar 2016 - GE Cour de justice (2016)
NOVA; RÉSILIATION ABUSIVE; FIDÉLITÉ; DONNÉES PERSONNELLES; INDEMNITÉ(EN GÉNÉRAL); GRATIFICATION; SALAIRE; PROTECTION DE LA PERSONNALITÉ | CO.336; CO.322d; CO.328